High-Speed Rail for Central and Eastern European Countries: A Conference Report - Monika Jandová; Zdeněk Tomeš; Chris Nash (Review of Economic Perspectives, 2016)
The European transport strategy promotes the role of railways and expects that the key role in passenger transport should be played by high-speed rail (HSR). Although the core network of high-speed lines has already been built and is operating in Western Europe, there has been little coverage so far in Central and Eastern Europe (CEE). The aim of the conference “High-Speed Rail for CEE Countries” that took place in Prague in June 2016 was to put together academics, policy-makers, and practitioners interested in HSR and to formulate recommendations for CEE countries based on West European countries' experience. Based on the conference presentations and subsequent discussion, the following conclusions were formulated. Firstly, there are many crucial differences in national HSR build-up and operation, which means that former experience of Western Europe is not directly applicable to CEE countries. Secondly, in comparing presentations discussing experiences in France, Britain, Italy, and Germany, it was concluded that the German approach-upgrading existing lines where possible and only building new lines for bottleneck sections-was the most likely appropriate solution in CEE. Lastly, CEE has the additional problem of many border crossings, with a reduction of traffic in comparison with purely domestic routes, and this effect has to be taken into account.
Keywords: 330; Central and Eastern Europe; demand forecast; ex-ante evaluations; economic geography; high-speed rail